An investigation on the power system stability of photovoltaic grid integrated system - Subramaniam T.; Rahman M.S.A.; Ariffin A.M.; Sahrim M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Control systems; Electric power generation; Electric power transmission networks; Fossil fuels; Photovoltaic cells; Power quality; Solar power generation; Voltage control; Conventional methods; Electricity generation; Generate electricity; NVSI; Photovoltaic systems; Power system stability; Solar photovoltaics; Voltage stability analysis; Electric power system stability